A dimensão moral do cuidar na educação infantil - Agulhare, Andressa Helena [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Present research investigated how morality has been developed from kinder garten through care relationships established between the nursery assistants, caregivers calls, and children aged 0-2 years old in order to identify if there the action of caring expressions of generosity, considered one of the virtues that are the genesis of human morality, as well as to analyze the conceptions of these nursery assistants about care as a possibility for the moral development of children. The research was based on theoretical studies of Jean Piaget (1932), a pioneer in psychological research on the development of moral judgment in children, and others who own research in the field of moral psychology related to the educational context as well as the care relationship with morality in order to support the research. The results show that the understanding of care in early child hood education is still superficial and based on concepts related to welfare, including caring in a limited way, just as an action aimed at the physical integrity of children. Unable to note concerns and moral development of children, taking care as a support. We hope this research instigate reflections on the importance of care in day care and their contributions to the moral awakening the children they serve

A presente pesquisa investigou como a moralidade vem sendo desenvolvida desde a Educação Infantil por meio das relações de cuidado que se estabelecem entre as auxiliares de creche, as chamadas cuidadoras, e as crianças da faixa etária de 0 a 2 anos de idade, buscando identificar se há a ação de cuidar expressões de generosidade, considerada uma das virtudes que constituem a gênese da moralidade humana, assim como analisar as concepções dessas auxiliares de creche sobre o cuidar como uma possibilidade para o desenvolvimento moral das crianças. A pesquisa teve como base teórica os estudos de Jean Piaget (1932), pioneiro nas investigações psicológicas sobre o desenvolvimento do juízo moral na criança, e outros autores que possuem pesquisas na área da psicologia moral relacionadas ao contexto educacional, assim como a relação do cuidado com a moralidade de modo a fundamentar a investigação. Os resultados revelam que o entendimento sobre o cuidar na educação infantil ainda é superficial e fundamentado em concepções ligadas ao assistencialismo, compreendendo o cuidado de forma limitada, apenas como uma ação voltada à integridade física das crianças. Não foi possível notar preocupações com o desenvolvimento moral das crianças tendo os cuidados como aporte. Esperamos que essa investigação instigue reflexões sobre a importância do cuidar na creche e suas contribuições ao despertar moral das crianças atendidas
Keywords: Avaliação educacional; Autonomia; Ética; Ensino fundamental; Desenvolvimento moral; Educação de crianças; Ludoterapia; Desenvolvimento cognitivo; Education Evaluation